Relation is as a Social Psychological Problem - Korayeva Latifa Zarifovna (Genius Journals, 2023)
This article discusses the main objectives of educational process; particularly issues related the improving of effectiveness of the educational process in the elementary school
Keywords: Internal and external activities; sensitive –cognitive behaviour